Pengaruh Model Pembelajaran Problem Based Learning Menggunakan Media Video terhadap Hasil Belajar Fisika Siswa - Jafri Haryadi; Dara Fitrah Dwi; Muhammad Sabdana (Departement of Mathematics Education, 2023)
Abstract Problem based learning model, students are required to solve the problems presented by digging up as much information as possible. Problem based learning is a learning that uses real-world problems presented at the beginning of learning, and then the problem is investigated to find out the solution. Video media as an illustration of the events of the material studied in the hope of providing a real picture of what was studied. This study aims to determine the influence of problem-based learning models by using video media to improve student learning outcomes in physics subjects. Sampling was carried out by random samples with a sample size of 60 students, 30 people for experimental classes and 30 people for control classes. The instrument used to determine student learning outcomes is a written test in the form of multiple choices totaling 25 questions with 4 answer options. The results of this study obtained an average value of the experimental class of 14.38 with a standard deviation of 3.63 and an average value of the control class of 10.03 with a standard deviation of 4.47. The data analysis technique uses the t test, and the results obtained t calculate > t table. The results of this study show the influence of problem-based learning models using video media on student physics learning outcomes.